Lethal and Sublethal Effects of Various Pesticides on Trichogramma achaeae (Hymenoptera: Trichogrammatidae) - Fontes, João (2019)
Little information is available regarding the lethal and sublethal effects of pesticides on Trichogramma achaeae (Nagaraja and Nagarkatti; Hymenoptera: Tricogrammatidae) during integrated management of Tuta absoluta (Meyrick; Lepidoptera: Gelechiidae), an important pest for tomato production. Twenty-two pesticides sprayed on Ephestia kuehniella (Zeller; Lepidoptera: Pyralidae) eggs were evaluated on the mortality of adult parasitoids upon contact with the hosts 24 h after the treatments and their sublethal effects on the parasitoids were assessed in laboratory conditions. Tests were carried out with fresh solutions at the recommended concentration. According to the International Organisation for Biological and Integrated Control (IOBC) standards, chlorpyrifos is harmful to the parasitoid; merthiocarb, methomyl, spinosad lambda-cyhalothrin, and acrinatrin are moderately harmful; and chlorantraniliprole, lufenuron, hexythiazox, cyromazine and Bacillus thuringiensis have no effect on the parasitoid. Sulfur is slightly harmful, and azoxystrobin is harmless. Chlorpyrifos was the most lethal among these pesticides and killed all females in less than 24 h. All other pesticides affected the biological parameters of T. achaeae to varying degrees. Regarding the lethal and sublethal effects, merthiocarb and spinosad killed all female offspring in less than 24 h; lambda-cyhalothrin and sulfur reduced the number of parasitized eggs; and acrinatrin, deltamethrin and azoxystrobin affected the emergence rate. After that, we can recommend the use of chlorantraniliprole and B. thuringiensis to control Lepidoptera, cyromazine to control Diptera, pirimicarb to control Homoptera, hexythiazox to control mites and azoxystrobin can be used as fungicide in an integrated pest management program with mass released of T. achaeae.